Global Research Patterns on Ground Penetrating Radar (GPR) - Gizzi, Fabrizio Terenzio; Leucci, Giovanni (Surveys in geophysics, 2018)
The article deals with the analysis of worldwide research patterns concerning ground penetrating radar (GPR) during 1995–2014. To do this, the Thomson Reuters’ Science Citation Index Expanded (SCI-EXPANDED) and the Social Sciences Citation Index accessed via the Web of Science Core Collection were the two bibliographic databases taken as a reference. We pay attention to the document typology and language, the publication trend and citations, the subject categories and journals, the collaborations between authors, the productivity of the authors, the most cited articles, the countries and the institutions involved, and other hot issues. Concerning the main research subfields involving GPR use, there were five, physical–mathematical, sedimentological–stratigraphical, civil engineering/engineering geology/cultural heritage, hydrological (HD), and glaciological (GL), subfields.